The advancement of human resource management in the new age / Sarah Sabir Ahmad and Azfahanee Zakaria - Sabir Ahmad, Sarah; Zakaria, Azfahanee (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
COVID-19 pandemic has greatly influenced how countries deal with it and simultaneously, it has impacted organizations in various ways too. Organizations have no choice but to adapt to the changing environment. One department that is highly affected by this pandemic is the human resource department. If previously, various responsibilities have been done in the traditional ways, now they have to be conducted in more modern and technologically advanced manners. When dealing with personnel, many considerations have to be done to ensure all parties are prepared to face the changes. This article highlights the impact and changes that the human resource department has to modify in order to keep the employees safe but also to ensure that the running of the organization is not interrupted to warrant the longevity of the organization.